2017
DOI: 10.15252/embj.201797397
|View full text |Cite
|
Sign up to set email alerts
|

APP mouse models for Alzheimer's disease preclinical studies

Abstract: Animal models of human diseases that accurately recapitulate clinical pathology are indispensable for understanding molecular mechanisms and advancing preclinical studies. The Alzheimer's disease (AD) research community has historically used first‐generation transgenic (Tg) mouse models that overexpress proteins linked to familial AD (FAD), mutant amyloid precursor protein (APP), or APP and presenilin (PS). These mice exhibit AD pathology, but the overexpression paradigm may cause additional phenotypes unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
593
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 598 publications
(617 citation statements)
references
References 148 publications
(204 reference statements)
18
593
0
6
Order By: Relevance
“…Lack of Congo red staining suggested that degree of amyloid accumulation is not as high in this Sgo1 −/+ model as existing EOAD mouse models that typically express a few‐to‐several‐fold amount of total amyloids compared with controls and show Congo red staining (Kitazawa et al., 2012; Onos et al., 2016; Sasaguri et al., 2016). The result was in agreement with immunoblots in Figure 1 indicating only mild increase in total amyloids (amyloid‐β and APP combined) in Sgo1 −/+ compared with age‐matched wild type and BubR1 −/+ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of Congo red staining suggested that degree of amyloid accumulation is not as high in this Sgo1 −/+ model as existing EOAD mouse models that typically express a few‐to‐several‐fold amount of total amyloids compared with controls and show Congo red staining (Kitazawa et al., 2012; Onos et al., 2016; Sasaguri et al., 2016). The result was in agreement with immunoblots in Figure 1 indicating only mild increase in total amyloids (amyloid‐β and APP combined) in Sgo1 −/+ compared with age‐matched wild type and BubR1 −/+ .…”
Section: Resultsmentioning
confidence: 99%
“…Major pathological features of the human AD brain include plaques of amyloid‐β made of cleaved APP, tangles of Tau proteins, and congophilic cerebral amyloid angiopathy (Kitazawa, Medeiros, & Laferl, 2012; Onos, Sukoff Rizzo, Howell, & Sasner, 2016; Sasaguri et al., 2016; Scheltens et al., 2016). With insufficient knowledge on the cause, modeling LOAD in rodents has been an issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The App-KI mice, which express humanized A with familial AD mutations at endogenous levels, exhibit AD-associated pathologies including pronounced A amyloidosis and gliosis (3) (4). In contrast, App-KI failed to reproduce some of the observations made using conventional mouse models (3)(4)(5) …”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on pathologic Aβ and subsequent alterations in synaptic and network activities have been using transgenic mouse models that overproduce mutant hAPP. Although these mouse models simulate several key aspects of human AD (Games et al, 1995; Hsiao et al, 1996; Sturchler-Pierrat et al, 1997; Götz et al, 2004; Cheng et al, 2007; Cissé et al, 2011; Verret et al, 2012), in these animals, Aβ and other APP fragments maybe overproduced and/or ectopically expressed (Chang and Suh, 2005; Mitani et al, 2012; Nicolas and Hassan, 2014; Kerridge et al, 2015; Nhan et al, 2015; Willem et al, 2015; Xia et al, 2016; Sasaguri et al, 2017). The App NL-F mouse model of AD was generated by manipulating the mouse App gene using a knock-in strategy (Nilsson et al, 2014; Saito et al, 2014), and this new mouse model is expected to advance our understanding of AD pathology.…”
Section: Introductionmentioning
confidence: 99%